Geomorfologia dos recifes submersos de Abrolhos e sua relação com as variações do nível relativo do mar - Ferreira, Lucas Cabral Lage (2017)
Abrolhos shelf has a great diversity of reef structures, such as fringing reefs, emerged reefs, pinnacles, reef banks and bioconstructions associated with paleychannels. Emerged reefs compose two reef arcs known as inner arc and outer arc. The submerged reefs extend from the inner shelf to the outer shelf and have been recently described. The goal of this study is show the morphology and spatial distribution of the Abrolhos submerged reefs in detail. To present a regional scale side-scan mapping of the shelf were collected 964 Km² of sonographic dataset. In addition we present unprecedentedly detailed mapping of pinnacles and reef banks morphology in the California reefs using multibeam bathymetry. Sonographic and bathymetric mosaic (4.5 x 9 Km²) were collected. Three reef patterns were defined: i) Pinnacles; (ii) Reef Banks and (iii) Bioconstructions Associated with Paleychannels. Pinnacles and reef banks were divided into High or Low Relief according with their shadows size in the sonographic records. These are the main reef structures and are wide distributed along the Abrolhos shelf. In the inner shelf (mainly in the Abrolhos Channel) the high relief reefs predominates. A transitional region is between 20 and 30 meters with High and Low Relief structures. The Low Relief banks predominate under 30 meters depth. The multibeam bathymetry made possible a detailed study of the submerged reefs morphology (height). In the California reefs the pinnacles presents great size variability with average height of 8.9 meters. Were mapped pinnacles with heights between 2 and 20 meters and average surface areas of 190,7 m². The banks have 2.7 meters height (average) and average surface areas of 8.608,8 m². Leao and Ginsburg, (1997) described the two emergent reef arcs, known as the inner arc and outer arc. In the region of the Abrolhos Channel presents the highest concentration of submerged structures, with predominance of high relief reefs. The region seaward outer arc is a region of transition from reefs of high relief to low relief and from the 30 meters predominate the reefs of low relief on the shelf. We suggest that the morphological change in the submerged reefs was conditioned by the last marine transgression. In the last glacial maximum the shelf was exposed and became to be progressively drowned. The Meltwater pulses (relatively quickly sea level rise) are the main agents that cause these submerged reefs drowning. The low-relief submerged banks are on the middle platform and have NE-SO alignment. Based on their morphology we suggest two hypotheses for their formation (i) they developed during the last marine transgression during a stabilization phase of sea level and later a rapid rise in sea level may have drowned these reefs; Ii) The banks would be "hardground" exposed and colonized by a mesophotic fauna. There are no ecological studies or dating in low relief banks, it is necessary to evaluate the ecological role of these reefs in the Abrolhos reef complex. Pinnacles also exhibit morphological changes in relation to the bathymetric gradient. Deeper pinnacles have columnar morphology and low growth rates when compared to high relief pinnacles.